2022
DOI: 10.1002/alz.12820
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for dementia in Brazil: Differences by region and race

Abstract: Introduction Twelve risk factors (RFs) account for 40% of dementia cases worldwide. However, most data for population attributable fractions (PAFs) are from high‐income countries (HIC). We estimated how much these RFs account for dementia cases in Brazil, stratifying estimates by race and socioeconomic level. Methods We calculated the prevalence and communalities of 12 RFs using 9412 Brazilian Longitudinal Study of Aging participants, then stratified according to self‐reported race and country macro‐regions. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 34 publications
2
58
0
Order By: Relevance
“…Nevertheless, 68.8% of older adults in LA have low education (less than 4 years) 5 . Moreover, it is estimated that 11.0% of dementia cases in LA are attributable to low education, with this estimate reaching 13.5% in Mexico and 7.7% in Brazil 5,6 . Our study shows that even at low levels, having more education is associated with reduced odds of cognitive impairment.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Nevertheless, 68.8% of older adults in LA have low education (less than 4 years) 5 . Moreover, it is estimated that 11.0% of dementia cases in LA are attributable to low education, with this estimate reaching 13.5% in Mexico and 7.7% in Brazil 5,6 . Our study shows that even at low levels, having more education is associated with reduced odds of cognitive impairment.…”
Section: Discussionmentioning
confidence: 56%
“…4 Low education was the most important risk factor for dementia in LA, with 7.7% of dementia cases attributable to lower education in Brazil and 13.5% in Mexico. 5,6 Cognitive reserve refers to the ability of the cognitive processes to withstand brain insult with little or no loss in performance. 7 Cognitive reserve is built over the life course through dynamic processes as a consequence of exposure to education, occupation, and leisuretime activities.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the two Brazilian cohorts showed opposite findings, the Bambui (Brazil) Cohort Study of Ageing showed a greater risk of dementia in women, and the São Paulo Aging & Health Study cohort showed the opposite, indicating that there may be other underlying explanations for the sex difference observed in dementia risk across different populations, including within‐country variation (e.g., urban vs. rural residence, area deprivation, or race). Notably, one recent study using nationally representative data in Brazil concluded that the overall weighted population attributable fraction (PAF) of RFs for dementia was larger in poor regions than rich regions, but the overall weighted PAFs were similar between different races 41 …”
Section: Discussionmentioning
confidence: 99%
“…Notably, one recent study using nationally representative data in Brazil concluded that the overall weighted population attributable fraction (PAF) of RFs for dementia was larger in poor regions than rich regions, but the overall weighted PAFs were similar between different races. 41 F I G U R E 2 Age-and education-adjusted study-specific and pooled hazard ratios for all-cause dementia by sex (women vs. men). CI, confidence interval; HR, hazard ratio After examining by birth year, which incorporated information on age and time periods, we found the sex difference in dementia risk was largely restricted to those born before 1925.…”
Section: Heterogeneity In Sex-specific Risk Of Dementiamentioning
confidence: 99%
“…Research shows that in LMIC 48% of dementia cases could be prevented if 12 modi able dementia-risk factors were controlled (Suemoto et al, 2022). Low educational level ranks highest among these factors.…”
Section: Introductionmentioning
confidence: 99%